The Effect of Spent Bleaching Earth Filler-Based NPK Fertilization on Proline, Growth and Yield of Maize - Ranggi Sumanjaya Purba; Siti Nurul Rofiqo Irwan; Eka Tarwaca Susila Putra (Caraka Tani: Journal of Sustainable Agriculture, 2020)
Spent bleaching earth (SBE) is by-product of cooking oil processing industry of crude palm oil (CPO). Palm oil industry is growing every year, followed by population growth and consumption of cooking oil so that the greater volume of waste generates SBE. An innovation is needed to anticipate the problem of SBE waste in agricultural sector, dealing with a filler component in the production of NPK fertilizer additives. This study aims to determine proline response, growth and yield of the maize to fertilization NPK with SBE-based filler. The experiments used Randomized Complete Block Design (RCBD) with the treatments of NPK filler (15:15:15) consisting of BC (brown clay), SBE and DBE (deoiled bleaching earth) at a dose of 6 g polybag-1. The results showed that the use of SBE gave the same effect on plant height, leaf number, stem diameter and 100-seed weight, but the use of SBE could increase 61.15% of proline activity. SBE can substitute filler on the additional materials of NPK fertilizer.